Retractıon Of Upper Incısors - Mustafa Kayalıoğlu; Üter Uzel; M. Serdar Toroğlu (Galenos Yayinevi, 2004)
Retraction of upper incisors in three dimensions of space has a striking effect on the aesthetic appearance of the face, on the function of the stomatognathic system and on the stability of the orthodontic treatment. Closing the extraction sites with the retraction of incisors is one of the most important stages in orthodontic treatment which involves extraction. Therefore, anchorage and retraction mechanics which will be applied in the orthodontic treatment should be planned exactly before the begining of the incisor retraction. It ought to be known that in which percentage the anatomic structures, particularly the palatal cortical bones, enable the upper incisor retraction, in which situation the resoption seen in upper incisors is formed and how the upper incisors can affect the profile of the face.